PEMBUATAN BIOETANOL DARI BIJI BINTARO (CERBERA manghas Lin.) DENGAN PROSES FERMENTASI RAGI DAN HIDROLISIS DENGAN ASAM SULFAT - Imas Solihat; Sri Redjeki Setyawati (Journal Warta AKAB, 2021)
The process of making bioethanol from Bintaro seeds (CERBERA manghas Lin.) has been carried out with a hydrolysis process through a sulfuric acid catalyst at a temperature of 60oC for 30 minutes and fermentation using yeast. Obtained glucose levels of 1.43% with 1.0 M sulfuric acid catalyst. For 30 minutes of hydrolysis time, a glucose level of 8.8% was obtained after the Bintaro seeds were fermented. Fermentation time for 5 days at a temperatur 100oC gives the ethanol content of 0.17%.